TEACHER TALKING TIME IN EFL CLASS - Dovhanets , Viktoriia (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
This study is aimed at understanding, explaining, and evaluating the effectiveness of Teacher Talking Time (TTT) and Student Talking Time (STT), that have become relevant in the context of a communicative approach in foreign languages teaching. The optimal balance of these components contributes to improving the quality of learning, enriching language skills of students, enhancing their understanding of a foreign language and the subsequent formation of students’ language competence. The considered teaching strategies include classroom management as well as teaching techniques that facilitate students in expressing themselves in meaningful ways through increasing interaction through pair work and team work.